Π-Extension improves the photovoltaic performance: a helical perylene diimide oligomer based three-dimensional non-fullerene acceptor. (18th September 2019) - Wu, Mingliang; Xia, Ping; Huang, Huaxi; Lin, Zhaohang; You, Xiaoxiao; Wang, Keke; Lu, Huan; Wu, Di; Xia, Jianlong
Abstract : A helical perylene diimide oligomer (PDI2) is gradually emerging as a promising building block for the construction of organic optoelectronic materials. Abstract : A helical perylene diimide oligomer (PDI2) is gradually emerging as a promising building block for the construction of organic optoelectronic materials. Motivated by the advancements made in earlier studies by our and other groups, in this contribution, a PDI2 tetramer based non-fullerene small molecule acceptor (SMA), namely SF-4PDI2, was designed and synthesized. Thanks to the orthogonal configuration of the 9, 9′-spirobifluorene (SF) core, the resultant SMA shows a highly twisted 3D geometry, which can avoid the formation of large crystalline domains and may result in a three-dimensional charge-transporting network. The optoelectronic properties of SF-4PDI2 have been systematically investigated. Using the commercially available PTB7-Th as the electron donor, a best PCE of 7.69% was achieved for the SF-4PDI2 based organic solar cells (OSCs), which is higher than that of the corresponding PDI tetramer-based ones. These results demonstrate that PDI2 is a promising alternative building block and shows magnificent potential in the photovoltaics field.